Aufnahme- und Entlassentscheidungen in der Psychiatrie: der 7-Tage-Zyklus : Analyse auf Grundlage der VIPP-Datenbank = Admission and discharge decisions in psychiatric hospitals : the 7-day cycle : analysis based on the VIPP database - Wolff-Menzler, Claus; Häfner, Sibylle (Der Nervenarzt, 2016)
SummaryBackgroundThe legislation requires all scientific societies in the field of inpatient psychiatric and psychosomatic healthcare to survey and assess the effects and financial incentives of the new flat rate day-based remuneration system in psychiatric and psychosomatic facilities (PEPP system). As day-based remuneration systems may be an incentive to extend treatment, it is necessary to measure and analyze the future development of the number of cases and the duration of treatment.ObjectivesThis article surveys admission and discharge decisions of psychiatric and psychosomatic facilities. The distribution of admissions and discharges throughout the days of the week were analyzed to search for evidence of a systematic extension of treatment over the weekend.Material and methodsThe analysis is based on data from the Versorgungsrelevante Indikatoren in der Psychiatrie und Psychosomatik (VIPP, treatment-relevant indicators in psychiatry and psychosomatics) project database, which contains routine data from psychiatric and psychosomatic facilities. On this basis the distributions of admissions and discharges throughout the days of the week were analyzed on aggregate and diagnosis-specific levels.ResultsPatients were mostly admitted to hospitals within the first 3 weekdays. The discharge mostly took place on Fridays and not as a financial incentive on Mondays. Regarding the patient length of stay a 7-day cycle can be observed, which may indicate the importance of medical and organizational factors in discharge decisions.ConclusionThe results do not show evidence for a systematic extension of treatment over the weekend. Over the next years it will be important to observe the development of the duration of treatment and the number of cases to assess the influence of the economic incentives of the PEPP system on the utilization of psychiatric and psychosomatic healthcare.